Evaluation of the effects of COVID‐19 disease and the trimester in which the disease is diagnosed on obstetric and neonatal outcomes: A retrospective cohort study. Issue 2 (24th November 2022) - Sertel, Emre; Demir, Merve
Abstract: Aim: To evaluate the effects of COVID‐19 disease and the trimester in which the disease is diagnosed on obstetric and neonatal outcomes. Methods: This retrospective cohort study was conducted with 358 patients who had or had not been diagnosed with COVID‐19 during their pregnancy, had a miscarriage or had given birth. Results: COVID‐19 disease during pregnancy was associated with higher maternal hypertensive disease, preterm birth, low birth weight, low first‐ and fifth‐minute Apgar scores, and need for neonatal intensive care unit. The incidence of preterm birth, low birth weight, low first‐ and fifth‐minute Apgar scores, and need for neonatal intensive care unit in those diagnosed with COVID‐19 in the second trimester was significantly higher than those diagnosed with COVID‐19 in other trimesters. The frequency of cesarean section was observed most in those diagnosed with COVID‐19 in the 3rd trimester, while it was observed in those diagnosed with COVID‐19 at least in the first trimester. Conclusion: The presence of COVID‐19 during pregnancy may be associated with an increased risk of iatrogenic preterm birth. The frequency of preterm birth in pregnant women diagnosed with COVID‐19 in the second trimester is higher than in pregnant women diagnosed with COVID‐19 in other trimesters. As the pregnancy trimester at the time of diagnosis progresses, the frequency of cesarean section increases. While the risk of maternal hypertensive disease increases more in pregnant women with COVID‐19, the effect of the trimester in which COVID‐19 was passed on the risk of maternal hypertensive disease is not observed.